E-063 Endovascular treatment of fusiform intracranial vertebral artery aneurysms using reconstructive techniques: single center experience. (4th July 2012) - Dabus, G; Samaniego, E; Linfante, I
Abstract : Objective: Fusiform intracranial aneurysms are challenging lesions that occur secondary to atherosclerosis or dissection. Although unclear, the prognosis of patients with fusiform aneurysms seems to be poor. We report our single center experience in the treatment of fusiform aneurysms involving the intracranial vertebral arteries using reconstructive endovascular techniques. Method: The neurointerventional database of our institution was retrospectively reviewed from June of 2010 to February of 2012. Patients who underwent endovascular treatment of fusiform intracranial vertebral artery aneurysms using reconstructive techniques were included in the analysis. Patients treated with parent vessel sacrifice (deconstructive technique) were excluded. Clinical presentation, size, reconstructive technique used, procedural complication, clinical and angiographic follow-ups were included in the analysis. Results: Seven patients met the inclusion criteria in our study. There were four men and three women with a mean age of 56 years (range 41–76 years). Two patients (two women) presented with acute subarachnoid hemorrhage (SAH) and were treated with stent assisted coil embolization (SACE). Five patients had unruptured aneurysms; four patients were treated with SACE; the other patient had a partially thrombosed aneurysm and was treated with stent-reconstruction with deployment of two stents (no coiling). The mean of the largest diameter of the lesions was 8.7 mm. There was one asymptomatic procedural complication (non-flow-limiting cervical dissection). All patients had good clinical outcomes (mRS <2) with no late hemorrhage at a mean clinical follow-up of 12 months. One patient that presented with SAH was lost to angiographic follow-up; for all other six patients angiographic follow-up was obtained (mean of 9.6 months). Of these patients, five demonstrated aneurysm occlusion with complete vessel reconstruction in the follow-up. One patient that presented with SAH and was treated with SACE had aneurysm regrowth at 1 month and was retreated with further coil embolization and deployment of a 3rd stent with no complications. Conclusions: The use of reconstructive techniques in the endovascular treatment of unruptured fusiform intracranial vertebral artery aneurysms is feasible, safe and effective in the mid-term. In patients presenting with SAH, however, the safety and effectiveness of these techniques remain unclear. Competing interests: G Dabus: Codman Neurovascular. Surpass Medical. E Samaniego: None. I Linfante: Codman Neurovascular. Surpass Medical.